Energy and lysine for broilers from 44 to 55 days of age - Araújo,LF (2005)
An experiment was conducted to evaluate the performance and carcass yield of broilers at 55 days of age fed diets with different levels of metabolizable energy and lysine. Evaluated data of performance were weight gain, feed intake, energy intake, lysine intake, caloric conversion and feed conversion. Carcass assessment was performed based on data from carcass yield, breast weight, whole wings, whole legs, back, head + neck, feet and abdominal fat. A 3 x 3 factorial arrangement was used, with 3 levels of metabolizable energy (3,200; 3,400 and 3,600 kcal ME/kg) and 3 lysine levels (0.95%; 1.05% and 1.15%). There was no interaction between the two factors. Nevertheless, increasing levels of metabolizable energy improved weight gain (745 g; 841 g and 910 g, respectively) and feed intake was higher in broilers receiving the diets with 3,200 and 3,600 kcal ME/kg. Overall performance was not affected by lysine levels. Feed conversion values were 2.69, 2.42 and 2.14 for birds fed diets with 3,200; 3,400 and 3,600 kcal ME/kg, respectively. Carcass yield and breast weight increased with higher levels of energy and lysine in the diets.